2020
DOI: 10.1007/s43440-020-00088-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the endocannabinoid system on the antidepressant activity of bupropion and moclobemide in the behavioural tests in mice

Abstract: Background Though there are several classes of antidepressant drugs available on the pharmaceutical market, depression that affects globally over 320 million people is still undertreated. Scientists have made attempts to develop novel therapeutical strategies to maximize effectiveness of therapy and minimize undesired reactions. One of the ideas is use of either dual-action agents or combined administration of two substances that affect diverse neurotransmissions. Thus, we investigated whether the selected CB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
7
0
1
Order By: Relevance
“…On the other hand, acute administration of CB2 antagonist/inverse agonist was shown to induce anxiogenic-like behavioral, whereas chronic pharmacological blockade of this receptor produced anxiolytic-like effects in parallel with increased expression of the CB2 in the amygdala and prefrontal cortex (García-Gutiérrez et al, 2012). In a recent study, the acute administration of the association of CB2 inverse agonist/antagonist, AM630, and atypical antidepressants (agomelatine and tianeptine) in ineffective doses, promoted antidepressant-like effects in the forced swimming test (Poleszak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, acute administration of CB2 antagonist/inverse agonist was shown to induce anxiogenic-like behavioral, whereas chronic pharmacological blockade of this receptor produced anxiolytic-like effects in parallel with increased expression of the CB2 in the amygdala and prefrontal cortex (García-Gutiérrez et al, 2012). In a recent study, the acute administration of the association of CB2 inverse agonist/antagonist, AM630, and atypical antidepressants (agomelatine and tianeptine) in ineffective doses, promoted antidepressant-like effects in the forced swimming test (Poleszak et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 2 decades, the endocannabinoid system (ECB), its receptors CB 1 and CB 2 ), and endogenous ligands (endocannabinoids) raised as one the major neuromodulator system controlling the fine tune of neurotransmitters (GABA, glutamate, monoamines) (Hájos et al, 2001;Wotjak, 2005;Mechoulam & Parker, 2013). As one of the most expressed G coupled receptors expressed in the brain, CB1 and CB2 receptors are current seeing as promising future targets and a missing link in the etiology of stress-related disorders, including their participation in the pharmacological effects of the current antidepressant (Hill et al, 2006;Poleszak et al, 2020) After its initial description in 1995, CB 2 was thought to be expressed mainly in peripheral cells of the immune system (e.g., lymphocytes and macrophages) (Ashton et al, 2006;Onaivi, 2006) and in the brain, restricted to pathological and neurodegenerative conditions such as gliomas (Sánchez et al, 2001); Alzheimer's disease (Benito et al, 2003), Multiple Sclerosis and Amyotrophic Lateral Sclerosis (Yiangou et al, 2006). Nowadays, the expression of CB 2 receptors in healthy brain cells remains controversial, and the current knowledge suggest that CB 2 gene and protein are expressed in microglial cells (Carlisle et al, 2002;Klegeris et al, 2003;Maresz et al, 2005) and in different brain regions, such as the striatum and hypothalamus of rats (Gong et al, 2006;Onaivi, 2006;Onaivi et al, 2008) and in the cingulate cortex, amygdala, hippocampus, hypothalamus, substantia nigra, dorsal and medial raphe of mice (Gong et al, 2006;Onaivi, 2006;Onaivi et al, 2008;García-Gutiérrez et al, 2010) These pieces of evidence suggest the distribution of CB 2 receptors in the CNS in brain areas responsible for emotional behavior and stress coping.…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that mice overexpressing CB2 receptors presented depressive‐like behaviours in FST and novelty‐suppressed feeding, which was reverted by chronic treatment with CB2 antagonist 56 . In agreement with these studies, the co‐administration of subeffective doses of different antidepressants (imipramine, escitalopram, reboxetine and bupropion) with both CB2 antagonist and agonist promoted an antidepressant‐like effect in FST and TST 57,58 . These contradictory results can reflect the participation of different populations of CB2 receptors, since they can be expressed in microglial cells, but also in presynaptic and postsynaptic neurons.…”
Section: Mechanisms Of 2‐ag Signalling In Stress and Depressionmentioning
confidence: 73%
“…Interestingly, plasma levels of either 2‐AG or AEA did not change during treatment with escitalopram. Animal models showed that modulation of CB1 receptors may boost the antidepressant activity of bupropion and moclobemide at cellular level (Poleszak et al., 2020), and that changes in EC‐metabolizing enzymes are induced by treatment with imipramine, escitalopram or tianeptine (Smaga, Gawlinski, Brodowicz, & Filip, 2019), Our study suggests that, at least in humans, serotonergic antidepressants do not modulate ECs, unless changes are highly localized or too small to be reflected by blood EC levels in the timeframe of the study. It can be hypothesized that different pathways are involved and that EC expression is not under the control of serotonergic transmission.…”
Section: Discussionmentioning
confidence: 99%